Parental Identity as a Predictor of Parental Involvement: The Mediating Role of Parent-Teacher Relationships among Ethnic Minority Parents - Zedan, Raed (Journal of Education Culture and Society, 2026)
Aim. This research aims to examine the contribution of a cohesive parental identity to parental involvement in school and the mediating role of the parent-teacher relationship among an ethnic-religious minority in Arab society in Israel. Methods. The study follows a quantitative research approach; a valid and reliable questionnaire was administered to 1,045 Israeli Arab parents. A descriptive and SEM statistical analysis was carried out. Results. A cohesive perception of parental identity was found to be associated with higher levels of parental involvement and higher quality of parent-teacher relationships. In addition, the quality of the parent-teacher relationship was found to be directly related to parental involvement and to mediate the relationship between parental identity and parental involvement. Conclusions. The findings emphasis the importance of strengthening parental identity and fostering positive parent-teacher relationships as a key means of increasing parental involvement in their children’s education, especially in the context of minority groups living in unique social conditions.